The Legal Rulings (Ahkam Al-Taklifiyah) in Surah Al-Isra: A Study in the Framework of Usul al-Fiqh - Khmees, Isra Sbea (Syura: Journal of Law, 2025)
This study explores the concept of Ahkam Al-Taklifiyah (obligatory legal rulings) and their applications as found in Surah Al-Isra, using the analytical framework of Usul al-Fiqh (principles of Islamic jurisprudence). The core issue addressed in this research is the need to comprehend how divine commands—both obligations and prohibitions—are manifested in the Qur'anic discourse and how they function as legal directives for human conduct. Specifically, this research seeks to examine the types and instances of Ahkam Al-Taklifiyah within Surah Al-Isra, highlighting their roles in shaping ethical and legal norms in Islamic law. The study employs a qualitative method through textual analysis (tahlil al-nass) by identifying, categorizing, and interpreting verses that represent legal rulings, such as commands (amr), prohibitions (nahy), permissions, and recommendations. Using the tools of Usul al-Fiqh, the research identifies the linguistic markers and contexts that signify each type of ruling. The findings reveal that Surah Al-Isra contains a significant concentration of legal-moral directives, including clear imperatives related to worship, social justice, and personal ethics. These rulings reflect the divine intention of regulating both individual and communal life through obligatory and prohibited actions. This research contributes to a deeper understanding of the integration between Qur'anic exegesis and Islamic legal theory, providing a model for legal-textual analysis within the Qur'an